THE MOTIVE FOR A DISTINCTION BETWEEN DONATUS OF CARTHAGE AND DONATUS OF CASAE NIGRAE - Alexander, J. S. (The journal of theological studies, 1980)
J. S. ALEXANDER; THE MOTIVE FOR A DISTINCTION BETWEEN DONATUS OF CARTHAGE AND DONATUS OF CASAE NIGRAE, The Journal of Theological Studies, Volume XXXI, Issue 2,